PENGARUH KEPUASAN KERJA, MOTIVASI KERJA DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN (STUDI KASUS KARYAWAN NON MEDIS DI RSUD LAWANG-MALANG) - Muhammad Idris; Hadi Sunaryo; M. Khoirul ABS (E-JRM : Elektronik Jurnal Riset Manajemen, 2019)
ABSTRACTThe study aims to study and analyze the impact of job satisfaction, motivation of work and organizational commitment to employee performance. Population and sample are all 32 employees. Data collection through questionnaire distribution. Analysis of the data in this study using SPSS version 16. The sampling technique using the census method and the data testing technique used in this research includes validity testing, reliability testing, classical hypothesis testing, multiple linear regression analysis, and hypothesis testing research.The results of the analysis show that the outline of job satifaction affects the significance of employee performance on motivattion of work that significantly influence employee performance as well as on organizational commitment has a significant effect. Together, it shows that job satisfaction, motivattion of work and organizational commitment significantly influence employee performance.Keywords: Job satisfaction,  Motivattion of Work and Organizational Commitment